Changing Business Models and Employee Representation in the Airline Industry: A Comparison of British Airways and Deutsche Lufthansa. (13th April 2015) - Lange, Knut; Geppert, Mike; Saka‐Helmhout, Ayse; Becker‐Ritterspach, Florian
<x xml:space="preserve">Abstract</x> In recent years, the notion of business models has gained momentum in management research. Scholars have discussed several barriers to changing business models in established firms. However, the national institutions of market economies have not yet been discussed as barriers, even though they can constrain the latitude of action of a firm's management. Based on interviews and a longitudinal content analysis, we analyse the extent to which full service carriers in two countries (British Airways in the UK and Deutsche Lufthansa in Germany) have adopted elements of a low cost model over time. Furthermore, we investigate how this process has been influenced by the differences in each national institutional context. We particularly focus on the role of the rights of employee representatives in changes in business models. Our results show that British Airways has moved its business model more in the direction of low cost carriers than Deutsche Lufthansa, although the business model of the former airline still differs significantly from that of a typical low cost carrier. We identify national institutions that potentially strengthen the position of employee representatives as a factor that can influence, and also act as a barrier to, business model change.